Expression of Catalase and Malondialdehyde Levels in Silicon Dioxyde-exposed Lung Tissue of Mice Treated with Moringa oleifera Leaves Extract - Kusmiyati, Kusmiyati; Keman, Soedjajadi; Amin, Muhammad; Suwarno, Suwarno (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Silica particle such as silicon dioxide (SiO2), is considered as a hazardous and cytotoxic particle. Silica particle exposure leads to oxidative stress in lung tissue. Moringa oleifera is a plant with potential antioxidant compounds. Therefore the aim of this study was to analyze the effect of M. oleifera leaves extract (MLE) on expression of catalase enzyme and malondialdehyde (MDA) levels in lung tissue of mice exposed to silica particles. This study was an experimental study with randomized posttest-only control group design using 30 male Balb/c strain mice, 8-10 weeks of age, 20-30 g body weight (BW), which were randomly divided into five groups. Group 1 was the negative control group, group 2 was exposed to SiO2 particle and set as the positive control group, group 3 was treated with MLE 2 mg/20 g BW, group 4 was treated with MLE 5 mg/20 g BW, and group 5 was treated with MLE 8 mg/20 g BW. After 90 days, mice were sacrificed by cervical dislocation and the lung tissues were examined.  Study results showed that expression of catalase in lung tissues of MLE-treated group was higher than that of positive control group, but not statistically significant. There was a significant difference of MDA level in lung tissue among groups. MDA level of groups treated with MLE 2 mg/20 g BW and 5 mg/20 g BW was lower than that of control group, while group treated with MLE 8 mg/20 g BW showed higher MDA level than control group (One Way ANOVA, p<0.05). It is concluded that administration of MLE indicates to prevent SiO2 inducedoxidative stress in lung tissue of Balb/c mice.    Keywords: Antioxidant, Catalase, Malondialdehyde, Moringa oleifera, Silicon dioxyde